2021
DOI: 10.1021/acs.jpcb.1c02276
|View full text |Cite
|
Sign up to set email alerts
|

Key Differences of the Hydrate Shell Structures of ATP and Mg·ATP Revealed by Terahertz Time-Domain Spectroscopy and Dynamic Light Scattering

Abstract: ATP is one of the main biological molecules. Many of its biological and physicochemical properties, such as energy capacity of the phosphate bonds, significantly depend on hydration. However, the structure of the hydration shell of the ATP molecule is still a matter of discussion. In this work, the hydration shells of ATP in water and MgCl 2 solutions were examined by terahertz time-domain spectroscopy and dynamic light scattering. Terahertz spectroscopy reveals the distorted water structure in the ATP water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
3
14
0
Order By: Relevance
“…Since the concentration of water molecules in the compared solutions is almost identical, a conclusion on the presence of a higher number of hydrogen bonds in the DNA hydration shells compared to undisturbed water can be drawn. An analogous result was obtained earlier in the work [ 30 ] on hydration shells of ATP molecules. We should note that the average number of hydrogen bonds with a water molecule in pure water at 25 °C comprises 3.6 of a possible 4 [ 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Since the concentration of water molecules in the compared solutions is almost identical, a conclusion on the presence of a higher number of hydrogen bonds in the DNA hydration shells compared to undisturbed water can be drawn. An analogous result was obtained earlier in the work [ 30 ] on hydration shells of ATP molecules. We should note that the average number of hydrogen bonds with a water molecule in pure water at 25 °C comprises 3.6 of a possible 4 [ 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is interesting to analyze the discussed regularities for DNA solutions compared to the ATP solution. An investigation devoted to studying the hydration shells of ATP by THz-TDS [ 30 ] demonstrated that the effect of ATP and Mg·ATP complex on water can be reduced to the decrease of Δ ε 1 and increase of Δ ε 2 and A/ ω 2 . Similar changes of the same parameters are also observed in the current work for DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the specifications of the THz spectral range corresponding to the intermolecular organization of water according to the specific times and energies. This is the only method sensitive to so-called dynamic hydration shells [ 42 , 45 , 56 , 57 , 58 ], which includes not just strongly bound water molecules in the primary layer, but also more distant molecules with slightly altered dynamics. In the case of aqueous sugar solutions, it is obviously confirmed by the fact that with increasing concentrations, the hydration number decreases starting from quite low concentrations, 0.15–0.3 M by monosaccharides [ 39 , 41 , 55 ].…”
Section: Introductionmentioning
confidence: 99%